1962
DOI: 10.1126/science.137.3532.765
|View full text |Cite
|
Sign up to set email alerts
|

Contamination of Vegetation by Tetraethyl Lead

Abstract: Tetraethyl lead is a normal constituent of vegetation growing along our highways. Washed grass near Denver contained 3000 ppm (in ash) near major intersections and > 50 ppm for 500 feet downwind. Vegetables grown within 25 feet of a road in upstate New York and western Maryland averaged 80 to 115 ppm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0
3

Year Published

1966
1966
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 185 publications
(39 citation statements)
references
References 1 publication
0
36
0
3
Order By: Relevance
“…The large concentration of airborne lead accumulates in soils (9, 33). Lead pollutants are incorporated into animal tissues (4,8) and have been shown to inhibit various enzyme systems (12,29,31,34).…”
Section: Introductionmentioning
confidence: 99%
“…The large concentration of airborne lead accumulates in soils (9, 33). Lead pollutants are incorporated into animal tissues (4,8) and have been shown to inhibit various enzyme systems (12,29,31,34).…”
Section: Introductionmentioning
confidence: 99%
“…The result of this process was a concentration of Pb deposits in the cell wall outside the plasmalemma. Similar deposits were observed in stems and leaves suggesting that Pb was transported and deposited in a similar manner.Many researchers have shown that plants will accumulate Pb either from soil, stem, or foliar application (1,3,8,9,13,14,16,25). However, the reports conflict as to the amounts accumulated and the amounts that can be translocated.…”
mentioning
confidence: 99%
“…In the open field, the Pb content of the upper 2 cm of soil declined from about 150 fig g" 1 at a point 0.3 m from the curb to 12 ng g" 1 at 18.3 m from the curb, and remained at that level to 30 m from the curb. In the 3 m between the curb and the near drip line of the windbreak, the Pb content of the soil diminished from 220 to 140 ng g" 1 . However, this range of Pb content was about 50% more than that of the open field at a similar distance from the road.…”
Section: Resultsmentioning
confidence: 99%
“…Commuter and truck traffic passed the windbreak at 65 to 73 km hr" 1 . A survey station maintained by the Connecticut Department of Transportation 1.6 km north of the windbreak recorded the traffic flow during 1973 (Table I).…”
Section: Traffic Flowmentioning
confidence: 99%